Compartmentalized minds: the Communist security services' understanding of the Western espionage threat to the Communist bloc during the Cold War. Issue 1 (2nd January 2021) - Maddrell, Paul
ABSTRACT: Marxism-Leninism required the counter-intelligence officers of the East German Stasi and Soviet KGB to believe in a Western espionage threat to their states which was far greater and more malevolent than was actually the case. In fact, the two counter-intelligence staffs knew that the Western states were trying to create small agent networks on their territory, tasked only with collecting intelligence. This accurate understanding enabled them to contain Western espionage during the Cold War. They 'compartmentalized' their knowledge of the real Western espionage threat from their belief in a much greater threat. They believed in one, but knew of another.